LINGUISTIC POLITENESS STRATEGIES USED BY LANGUAGE TEACHERS FOR EFFECTIVE CLASSROOM COMMUNICATION - Ida Bagus Nyoman Mantra (Media Bina Ilmiah, 2024)
The code of conduct established by a specific community and accepted as necessary for a peaceful living environment is known as politeness. Being courteous involves more than just acting appropriately; it also involves communicating with proper language. A speaker might lessen the undesirable outcomes by employing politeness techniques. This study intended to examine the many forms of linguistic politeness that language teachers use in classroom communication. In this study, descriptive analysis was combined with a qualitative research design. The study's findings suggested that there were specific basic rules for language politeness and positive and negative politeness techniques for putting them into practice. Therefore, teachers are expected to continually use polite forms of language to create a conducive learning environment